Regional Development in an Ageing Society: Overview of Selected Foreign and Polish Recommendations and Practices - Andrzej Klimczuk (Aktywna starość w perspektywie społeczno-kulturowo-edukacyjnej / Společenské, kulturní a vzdělávací aspekty fenoménu aktivního stárnutí, 2015)
The complexity of population ageing effect is a significant challenge at a regional and local level. Adaptation activities require the cooperation of local governments, business entities and non-governmental organizations. The article describes the dimensions of interventions, typology of “shrinking regions” and two initiatives: Regions for All Ages and SEN@ER - Silver Economy Network of European Regions. In addition, essay discusses the dilemmas of creating special regional strategies with their implementation factors and barriers in the construction of silver economies. It is supplemented by some conclusions from the analysis of selected regional development strategies in Poland. Summary sets out possible directions for further research for national institutions.
Keywords: J14; O18; P48; R58; 330; Regions for All Ages; Silver Market; Silver Economy; Shrinking Regions; Cross-Sector Cooperation; Local and Regional Development; Social cohesion